Post Operative Pulmonary Complications Following Surgery for Congenital Heart Disease - Hasan, M Nurul Akhtar; Sharifuzzaman, M; Shamsuddin, Abul Kalam; Biswas, Samir Kumar; Hossain, Jesmin; Sheikh, Mohammad Rahamat Ali (Journal of Bangladesh College of Physicians and Surgeons, 2017)
Objective: To identify the incidence and related factors for pulmonary complications and its impact on outcome in patients subjected to surgery for congenital heart disease (CHD). Methods: The sample comprised 141 patients of both genders, subjected to surgery for CHD, during 3 months period from 1st July 2014 to 30th September 2014. The data were obtained from newly improvised Congenital Heart Surgery Database. Results: Twenty eight (20%) patients developed some form of pulmonary complications. Age, weight, length and body surface area are significantly low among them (p <0.05). They also have higher Aristotle score & RACHS score, higher CPB time and aortic cross clamp time (p <0.01). Patients who had pulmonary complications had significantly higher (p <0.01) vasoactive inotrope score, prolonged mechanical ventilation, longer post operative ICU stay and post operative hospital stay. There was no mortality. Conclusions: Pulmonary complications are common after surgery for CHD which is more common in small children and complex surgeries. It significantly affects outcome including duration of mechanical ventilation and length of stay but no effect in mortality. J Bangladesh Coll Phys Surg 2017; 35(2): 52-60